Does Load‐Induced Shallow Subsidence Inhibit Delta Growth?. Issue 11 (7th November 2021) - Chamberlain, E. L.; Shen, Z.; Kim, W.; McKinley, S.; Anderson, S.; Törnqvist, T. E.
Abstract: The ability of deltas to persist by building new land is critical to maintaining these vital ecologic environments that are often home to major economic and population centers. However, the deposition of land‐building sediment triggers load‐induced shallow subsidence which may undermine the effectiveness of natural and engineered emergent landforms. Here, we present a new method to quantify shallow subsidence in a 6, 000–8, 000 km 2 relict bayhead delta of the Mississippi Delta using the mouth bar to overbank stratigraphic boundary that formed near sea level, temporally constrained by optically stimulated luminescence dating. Vertical displacement rates at this boundary, averaged over 750–1, 500 years, are on the order of a few mm/yr. Total subsidence scales to ∼50% of the thickness of overlying deposits, significantly greater than the 28%–35% loss estimated for inland localities underlain by peat, indicating that bay muds in the study area are more compaction‐prone than terrestrial organic‐rich deposits. Modeling shows a modest reduction of ∼13% in deltaic land‐area gain under a realistic compaction scenario for 1, 000 years of simulated delta progradation, compared to a no‐compaction scenario. Our findings indicate that load‐driven compaction does not majorly hinder land‐area gain and may in fact promote long‐term growth at engineered sediment diversions through channel maintenance driven by compaction, thereby adding further support to this restoration strategy. Plain Language Summary: Deltas naturally lose elevation with time, and this loss must be balanced by new deposition or growth to maintain the land area. However, the deposition of sand and mud may drive further elevation loss due to its weight acting on underlying deposits. We use a new method to extract information about the relationship between sediment loading and elevation loss using the sedimentary archive of an abandoned lobe in the Mississippi Delta. We show that coastal regions characterized by delta growth into open water, like our study area, are particularly prone to elevation loss. Nevertheless, we find that engineering solutions to build new land in deltas are still viable. Key Points: Mouth‐bar surfaces are common stratigraphic features in river‐dominated deltas that represent an unexplored relative sea‐level indicator Bayfloor muds may be more vulnerable to load‐induced sediment compaction than peats in the Mississippi Delta Load‐induced subsidence has a limited impact on delta progradation and may stabilize distributary channels